ANALISIS KEMAMPUAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL HIGH ORDER THINKING SKILS (HOTS) PADA MUATAN PPKN KELAS VI UPTD SD NEGERI MOEPALI - LalangYame, Jon abraham; Imanuel Puling; Evi Vania Paduwal; Gladys Itunde (STKIP Subang, 2026)
Analysis of Students' Ability to Solve High-Order Thinking Skills (HOTS) Questions in the Civics Content of Grade V at the Moepali Public Elementary School Technical Implementation Unit (UPTD) for the 2024/2025 Academic Year. This study aims to describe students' ability to solve High-Order Thinking Skills (HOTS) questions in the Civics Content of Grade V at the Moepali Public Elementary School Technical Implementation Unit (UPTD). This study employed a qualitative approach with a descriptive approach. Data collection methods included interviews, tests, and documentation. The subjects were sixth-grade homeroom teachers and sixth-grade student work. Data were collected through interviews with homeroom teachers and analysis of student test results compiled based on Bloom's Taxonomy. The analysis showed that 100% of the questions used were at a high cognitive level, specifically critical thinking skills, with an average student success rate of 75% in answering HOTS questions. This study indicates that although there has been an increase in higher-order thinking skills, efforts are still needed to improve students' analytical and creative abilities.